Switch test method of train communication network based on Ethernet - YANG Peng (机车电传动)
As the node of train network data gathering, storage and transmit which based on Ethernet, switches have been the core equipment of train network communication and control. By analyzing the application requirements of train control and diagnosis based on train communication network topology and Ethernet, and concluding the services to be provided by ETB and ECN switches, a function and performance test method for ETB switch and ECN switch was raised, which could cover the physical layer, data link layer, the network layer, the transport layer and the application layer. The physical layer was based on the general test method of electronic products of the rolling stock. The data link layer and network layer adopted throughput, latency, back-to-back tests, and tests based on the requirement of QoS and ARP. The transport layer and the application layer adopted end-to-end data communication test, IGMP test and SNMP test, with the detailed test configuration and steps. The test method could meet the requirements of real-time, security and reliability of switches in TCN based on Ethernet. At last, taking an ECN managed consist switch as an example, the test evaluation scheme was introduced. The scheme fully met the performance testing requirements of the layer 2 or layer 3 switches interface test. It also met the test requirements of process data, message data, best effort data transmission in the train network, and the test requirements of related protocols. By standardizing the test method, a new solution for Ethernet switch performance consistency control was provided.